Standardisation of vanilla curing techniques - MANJUSHA MATHEW ROSHNI RAJU SHAILESH KUMAR SINGH; Dr. K. P Sudheer (Guide) (Tavanur 2005 Kelappaji College of Agricultural Engineering and Technology)
first method bourbon method second method consisted of killing using hot water followed by low temperature mechanical drying and the final moisture content and reduction in thickness was observed.
Standardization of vanilla curing techniques